2011
DOI: 10.1111/j.1758-5910.2011.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Pure laparoscopic hepatectomy for hepatocellular carcinoma patients with severe liver cirrhosis

Abstract: Hepatocellular carcinoma often arises in cirrhotic livers. Patients with severe liver cirrhosis who undergo hepatectomy often develop postoperative liver failure, even if the hepatectomy is limited. Here, we report six patients with severe liver cirrhosis (Child-Pugh B/C and indocyanine green retention rate at 15 min ≥ 40%) who underwent pure laparoscopic hepatectomy. Their perioperative course was favorable and comparable to that of other hepatocellular carcinoma patients with mild-moderate liver cirrhosis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…A key aim of our LLR is to carry out minimum dissection of the attachments and adhesions around the liver, in order to minimize the risk of damage to the environment around the liver. Most of our LLR patients have HCC/CLD and, occasionally, severe CLD patients undergo LLR[35]; this is partially due to the well-recognized situation in Japan involving a shortage of cadaver donors. Damage to the proximal environment associated with liver resection, such as dissection-related destruction of collateral venous/lymphatic flows, can easily lead to massive ascites and liver failure.…”
Section: Our Approach: Caudal Approach With Postural Changesmentioning
confidence: 99%
“…A key aim of our LLR is to carry out minimum dissection of the attachments and adhesions around the liver, in order to minimize the risk of damage to the environment around the liver. Most of our LLR patients have HCC/CLD and, occasionally, severe CLD patients undergo LLR[35]; this is partially due to the well-recognized situation in Japan involving a shortage of cadaver donors. Damage to the proximal environment associated with liver resection, such as dissection-related destruction of collateral venous/lymphatic flows, can easily lead to massive ascites and liver failure.…”
Section: Our Approach: Caudal Approach With Postural Changesmentioning
confidence: 99%
“…We also experienced that the perioperative course of HCC patients with severe liver cirrhosis (Child-Pugh class B/C and ICG R15 of ≥ 40%) who underwent pure laparoscopic hepatectomy was favorable and comparable to that of the other HCC patients with mild/moderate liver cirrhosis [40] . As of 2012, 40 patients with HCC and chronic liver disease underwent pure laparoscopic hepatectomy in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] Thus, LLR limits the occurrence of complications, such as massive ascites, which can lead to postoperative liver failure. [3] We also reported that the smaller working space required for LLR necessitated less adhesiolysis, with a direct approach to the region affected by the tumor being possible in repeat LLR.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] The deterioration of liver function should be minimized with the reduced adhesiolysis and dissection required during a laparoscopic approach. In addition, LLR better prepared patients both physically and psychologically for a subsequent repeat LR, illustrated by a shortened hospital stay for the patient reported here.…”
Section: Discussionmentioning
confidence: 99%